Strengthening Quality Assurance Through Community Needs-Based Learning at PKBM Al-Amin Rao Selatan, Pasaman Regency - Anisa Fitriani; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analyze the strengthening of quality assurance through community-based learning at PKBM Al-Amin Rao Selatan, Pasaman Regency, West Sumatra. The study uses a descriptive qualitative approach with data collection techniques through literature studies and observations. The results of the study indicate that the implementation of needs-based learning can increase program relevance, student participation, and the effectiveness of learning outcomes. In addition, the integration of andragogical principles, participatory learning, and continuous evaluation strengthens the institution's internal quality assurance system. These findings confirm that the quality of non- formal education is not only determined by administrative standards, but by the active involvement of the community in the entire learning process.